INTEGRASI USHUL FIQH, KAIDAH FIQH DAN FIQH IQTISHADI DALAM PRAKTIK LETTER OF CREDIT SEBAGAI TELAAH KONSEPTUAL DAN APLIKATIF - Yuni Mayanti; Yasir Muharram Fauzi; Amelia Dewi Purwanti; Bahmid Imagi (KASBANA, 2026)
Abstract This study aims to examine the integration of Usul Fiqh, Fiqh Principles, and Iqtishadi Fiqh in the practice of Letter of Credit (L/C) as an international trade financing instrument. From an Islamic economic perspective, L/C transactions involving multiple parties and contractual agreements require in-depth analysis from an Islamic legal perspective to ensure compliance with sharia principles. Ushul Fiqh provides a methodological framework for understanding legal arguments, while Fiqh Principles offer general principles that guide legal istinbat on various contemporary issues. Iqtishadi Fiqh, as a branch of fiqh that focuses on economic issues, becomes an applicable domain for the application of both disciplines. This study uses a descriptive qualitative approach with literature study as the main method. The results of the study indicate that L/C is acceptable in the Islamic economic system as long as it meets the requirements and pillars of the contract and avoids elements of riba, gharar, and maisir. Thus, the conceptual and practical integration of the three pillars of Islamic law (Ushul Fiqh, Fiqh principles, and Iqtishadi Fiqh) demonstrates that Islamic law has the flexibility and capacity to address modern economic challenges in a just, relevant, and sustainable manner. The results of this study open up opportunities for further development of Islamic financial fatwas and policies based on a comprehensive methodological understanding. Keywords: Ushul Fiqh, Kaidah Fiqh, Fiqh Iqtishadi, Letter of  Credit